Puta ang ina mo! concept of prostitution of the children of sex workers: Their self-esteem, self perception and hope - Bernardino, Michael B. (Animo Repository, 2010)
The study is quantitative and qualitative in nature that aimed to know the concept of prostitution by the children of the sex workers through their self-esteem, self-perception, and hope. The researchers gathered 20 respondents from Batangas City and Subic, Olongapo City whose age are 12 years old and above and whose mothers are a sex worker. Cooleys Self-Looking Glass, Hope Interview and Rosenberg Self-Esteem Likert-Type Scale were used as instruments in the research methods. The respondents neither have high nor low self-esteem. Despite being a child of a sex worker, the respondents have reported that they have learned to accept the nature of their mothers job while being hopeful that someday they would still be able to have a better life through education and an aspired work.